Sentiment on Public Trust Using the NLP Rule Based Method - Sipayung, Evasaria Magdalena (Jurusan Informatika Universitas Tanjungpura, 2024)
Government policy is understood from suggestions that will be achieved or regulated where the target is the public in the sense of society and the public interest, then government policy can be categorized as public policy. The policies implemented by the Government in 2022 include the stages of eliminating Premium and Pertalite fuel oil, increasing the price of non-subsidized LPG gas, the application of BPJS standard classes, and fishing is limited through a quota system. In this research, government policy sentiment analysis was carried out using the NLP (Natural Language Processing) method on tweet data. There are three policies that serve as a reference for public trust, namely the